Microbial Warfare on Three Fronts: Mixed Biofilm of Aspergillus fumigatus and Staphylococcus aureus on Primary Cultures of Human Limbo-Corneal Fibroblasts - Ramírez-Granillo, Adrián; Bautista-Hernández, Luis Antonio; Bautista-De Lucío, Víctor Manuel; Magaña-Guerrero, Fátima Sofía; Domínguez-López, Alfredo; Córdova-Alcántara, Itzel Margarita; Pérez, Néstor O.; Martínez-Rivera, María de los Angeles; Rodríguez-Tovar, Aída Verónica (Frontiers in Cellular and Infection Microbiology, 2021)
Background. Co-infections with fungus and bacteria reported in ocular pathologies are increasing at an alarming rate. Mixed fungal-bacterial biofilms (MFBB) are rarely reported in ocular infections. Two of the main etiological agents of infections on the corneal surface, such as A. fumigatus (Af) and S. aureus (Sa) have shown an increase in the incidence in recent years are able to form biofilm. The implementation of cell cultures as a study model related to biofilm microbial keratitis will allow us to understand the pathogenesis in the cornea. The cornea maintains pathogen-free ocular surface. Human limbocorneal fibroblast cells (HLFC) are a critical part of the cell regeneration process in the cornea. There are no reports of biofilm formation assays on HLFC, as well as, their behavior with a polymicrobial infection. Objective. To determine the capacity of biofilm formation during the fungus-bacteria interaction (FBI) of A. fumigatus and S. aureus on primary HLFC cultures. Results. Biofilm in HLFC in vitro culture was analyzed, evaluating the biomass production and determining the metabolic activity. Furthermore, the biofilm producing effect by FBI in this cell culture was monitored with several microscopies. Production of biofilm in monoculture and polymicrobial culture is higher on HLFC than abiotic surfaces. The Af biofilm over HLFC culture showed a considerable decrease compared to the Sa biofilm on HLFC monolayer. Moreover, the Af+Sa biofilm was determined showing that polymicrobial biofilm is has lower density than in microbial monocultures. Antibiosis between Af and Sa persists during the challenge to HLFC, but it seems that the fungus was more effectively inhibited. Conclusion. First report of MFBB production and morphological characterization of this biofilm over HLFCs. Three antibiosis behaviors were observed between fungi, bacteria and HLFCs. The antibiosis over Af is exacerbated on the culture of HLFC and it have an antagonic mycophagic effect by Sa. During FBI appears that HLFC showed some phagocytic activity. Demonstrating tripartite relationships during co-infection.